Projected inhibition of platelet aggregation with ticagrelor twice daily vs. clopidogrel once daily based on patient adherence data (the TWICE project). (May 2014) - Vrijens, Bernard; Claeys, Marc J.; Legrand, Victor; Vandendriessche, Eef; Van de Werf, Frans
<x xml:space="preserve">Abstract</x> Aim Twice daily dosing is often perceived as inferior to once daily dosing due to a higher likelihood of missing a dose. However, more important is the extent to which drug action is maintained when doses are delayed or missed. We compared the estimated inhibition of platelet aggregation (eIPA) for ticagrelor twice daily and clopidogrel once daily, based on their pharmacokinetic/pharmacodynamic relationships and patient dosing history data. Methods Drug dosing histories of 5014 patients prescribed cardiovascular medications (primarily antihypertensive medicines) were extracted from an electronically compiled dosing history database. eIPA levels were simulated for 677 twice daily and 677 once daily dosing histories over a 30 day period, based on published onset/offset models for ticagrelor and clopidogrel IPA characteristics. Results While many patients treated twice daily missed at least one dose in 30 days, only 25.7% missed two consecutive doses. By comparison, 46.8% of patients treated once daily missed at least one dose. Simulations based on patient adherence over time showed that the average mean eIPA for ticagrelor twice daily remained significantly higher than for clopidogrel once daily (81.1% vs. 55.0%, P < 0.001). Ticagrelor twice daily patients had an eIPA below 10% for 0.20% of the 30 day period compared with 2.05% for clopidogrel once daily (P = 0.0001). Conclusions The projected level of platelet inhibition remained higher for ticagrelor twice daily than clopidogrel once daily, mainly due to the higher eIPA level achieved with ticagrelor and the relatively low likelihood of missing two consecutive twice daily doses. This modelling and simulation study suggests a therapeutic benefit of ticagrelor over clopidogrel when taking into account the most common dosing omissions.